Inter-organisational knowledge spillovers: attracting talent in science and technology parks and corporate social responsibility practices. Issue 5 (13th June 2019) - González-Masip, Jaime; Martín-de Castro, Gregorio; Hernández, Adolfo
Abstract : Purpose: This paper aims to propose that firms located in science and technology parks (STP) developing corporate social responsibility practices can attract talented workers as an effective knowledge management spillover mechanism. Design/methodology/approach: A longitudinal study has been carried out from the Spanish Panel of Technological Innovation database (PITEC). The statistical method used for data treatment has been a logistic regression for panel data. Findings: Empirical results show a positive moderating effect of corporate social responsibility practices on the relationship between the firm's belonging to a STP and talent attraction. Originality/value: This research follows previous claim for additional research on the phenomenon of talent management and clusters and STP. In that sense, and to the best of the authors' knowledge, there is no previous empirical research about the complementarily effect of corporate social responsibility practices and the belonging to a STP in talent attraction.